Modelling Location Decisions - The role of R&D activities - Isabel Mota; António Brand\~ao (European Regional Science Association (ERSA), 2005)
In this essay, we intend to evaluate the importance of R&D (Research and Development) activities for firms' decision about location. For that purpose, we use micro-level data for the Portuguese industrial sector and focus on the location choices made by new starting firms during 1992-2000 within 275 municipalities. We consider two samples: the first one includes the entire manufacturer sector, while the second one restricts for those industrial branches that were R&D intensive. The set of explanatory variables includes a group of technological variables, such as R&D expenditures and human capital stock, as well as other explanatory variables that account for location specific characteristics and that are traditionally stressed by urban and regional theory, such as production costs (labor costs, land costs and taxes), demand indicators and agglomeration economies (urbanization and localization economies). The model is based on the random utility maximization framework but proceeds through a Poisson regression model for panel data, due to its equivalence with the conditional logit model. Through the estimation of the model, we were able to conclude that for the entire manufacturer sector, the main determinants for location decisions were the labor and land costs and the localization and urbanization economies. However, when considering the R&D intensive sample, those traditional location determinants lose importance, whilst the technological variables, such as the R&D expenditures, become relevant.
Keywords: 330